TWO PATIENTS WITH TRANSIENT GLOBAL AMNESIA IN WHICH REPEATED DIFFUSION-WEIGHTED IMAGING REVEALED HIPPOCAMPAL HYPERINTENSITY: CASE REPORTS - Turgay Dölek; Utku Cenikli; Vedat Semai Bek; Gülnihal Kutlu Günergin (İstanbul Tıp Fakültesi Dergisi)
An episode of temporary memory loss which is recovered within 24 hours is called transient global amnesia. The etiology and triggering factors are unclear but hippocampal lesions may contribute to this condition. Diffusion-weighted magnetic resonance imaging is used to detect these lesions. In this case report, two cases with transient global amnesia who had hippocampal lesions are presented.